2020
DOI: 10.1101/2020.09.21.20199109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nature and dimensions of the cytokine storm and its attenuation by convalescent plasma in severe COVID-19

Abstract: In a randomized control trial on convalescent plasma therapy (CPT) in severe COVID-19, we characterized the nature, in terms of abundance of forty eight cytokines, and dimensions, in terms of their interrelationships, of the hyper-immune activation-associated cytokine storm in patients suffering from acute respiratory distress syndrome. We found plasma MCP3 level to be a key correlate for mitigation of hypoxia, irrespective of therapeutic regimen. We also identified an anti-inflammatory role of CPT independen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The severe COVID-19 patients have been found by previous studies to experience a systemic immune hyper-activation characterized by a cytokine storm. We had previously reported nature and dimension of the cytokine storm in a fraction of these patients, comparing them to patients suffering from mild COVID-19 disease (Bandopadhyay et al, 2020). On measuring plasma abundance of a panel of 48 cytokines in patients from both arms we found that correlative nature and magnitude of the individual components of the cytokine storm were not notably different at T1 in a correlative network analysis (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The severe COVID-19 patients have been found by previous studies to experience a systemic immune hyper-activation characterized by a cytokine storm. We had previously reported nature and dimension of the cytokine storm in a fraction of these patients, comparing them to patients suffering from mild COVID-19 disease (Bandopadhyay et al, 2020). On measuring plasma abundance of a panel of 48 cytokines in patients from both arms we found that correlative nature and magnitude of the individual components of the cytokine storm were not notably different at T1 in a correlative network analysis (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, convalescent plasma transfusion is associated with reductions in inflammatory markers, such as chemokines, cytokines and C-reactive protein. 44,57 Concomitant reductions in inflammation and improved gas exchange may underlie the reductions in oxygen requirements associated with convalescent plasma, even in critically ill patients. These findings provide mechanistic evidence for the reduction in mortality observed in patients receiving convalescent plasma.…”
Section: Resultsmentioning
confidence: 99%
“…• Patients treated with CCP manifest reduced inflammatory markers [35][36][37] that can lead to host damage. 38 • Research has identified nine places where plasma affects the cascade of inflammation to the benefit of treated patients 39 .…”
Section: Discussionmentioning
confidence: 99%